Investigation of Physico-Chemical Properties of Simaruoba Methyl Ester and Diesel Blends - R. Hosmani, Basavaraj; V. Katti, Vadiraj (International Journal of Engineering and Technology, 2018)
This paper presents the experimental study of physico-chemical properties of Simarouba methyl ester and diesel blends at the different temperatures and with varying volume percentage of Simarouba methyl ester in the blend. Blends are prepared adding different volume fraction of Simarouba methyl ester to neat diesel. The percentage of Simarouba methyl ester added to diesel is 10% to 90%, the prepared blends are stirred well for mixing of methyl ester and diesel. The prepared blends are kept in closed container for 24 hours for observation of separation of blends. It is observed that there is no separation of Simarouba methyl ester and diesel. Experiments are carried out to find density, kinematic viscosity, flash point and heating value of blends. These properties are investigated using standard equipments with standard procedure. Viscosity is determined by using standard Red-Wood viscometer with standard procedure of methyl ester and diesel blends at different temperatures. It is observed that as volume fraction of Simarouba methyl ester increases in the blend density, kinematic viscosity, flash point increases and heating value decreases. The percentage decrease in kinematic viscosity is more at lower temperature compared to higher temperature. Correlations for estimation of viscosity and density of blends at different temperatures are proposed.Â Â
Keywords: blends; calorific value; density; Simarouba methyl ester; viscosity.